Software-based decision-support : a basis for the development of a predictive system for sustainable management of haemonchosis in small ruminants - Boomker, Jacob Diederik Frederik (University of Pretoria, 2013)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2007.